Rancangan Sistem Informasi Penilaian Kinerja Karyawan Berbasis Proses Bisnis - Aulianisa, Ridha; Yunani, Akhmad (Jurnal Syntax Fusion, 2023)
Employee performance appraisal is one that must be considered by a company in order to support employee performance evaluation and business processes that occur within the company. The process of identifying and evaluating the level of HR excellence can be obtained through a performance appraisal process. One of them is in a company engaged in the financial planning service industry, PT. My finances, which are still guided by manual Self Appraisal assessment for complete the performance appraisal process. This is the background of the author so that a business process-based employee performance appraisal design is made to make performance appraisals more effective and efficient. This research is a descriptive qualitative research that provides an overview of the company's internal conditions and describes the design of an employee performance appraisal system in accordance with the current performance appraisal process. The data validity technique used is triangulation technique to test credibility. In designing a business process-based performance appraisal system, there are three main processes, namely the input stage, the process stage and the output stage. The result of this research is the design of an employee performance appraisal system based on a business process that is objective, effective, efficient and avoids repetition of work. So that the HRD team can focus on maximizing the design of training programs for the development of my Financial HR in order to advance and support the company's growth.